Editorial: molecular eavesdropping: phagocytic cells spy on bacterial communication - Hänsch, Gertrud Maria (Journal of leukocyte biology, 2012)
Journal of Leukocyte Biology considers manuscripts of original investigations focusing on the origins, developmental biology, biochemistry and functions of granulocytes, lymphocytes, mononuclear phagocytes, and other cells involved in host defense. These include full-length papers on original research, rapid communications of new discoveries, letters, commentaries, and invited reviews.